Β‐Sitosterol Enhances Cellular Glutathione Redox Cycling by Reactive Oxygen Species Generated From Mitochondrial Respiration: Protection Against Oxidant Injury in H9c2 Cells and Rat Hearts. (26th November 2013) - Wong, Hoi Shan; Chen, Na; Leong, Pou Kuan; Ko, Kam Ming
<x xml:space="preserve">Abstract</x> Herba Cistanches (Cistanche deserticola Y. C. Ma) is a 'Yang‐invigorating' tonic herb in Chinese medicine. Preliminary chemical analysis indicated that β‐sitosterol (BS) is one of the chemical constituents in an active fraction of Herba Cistanches. To investigate whether BS is an active ingredient of Herba Cistanches, the effects of BS on H9c2 cells and rat hearts were examined. The results indicated that BS stimulated the mitochondrial ATP generation capacity in H9c2 cells, which was associated with the increased production of mitochondrial reactive oxygen species. BS also stimulated mitochondrial state 3 and state 4 respiration, with the resultant decrease in coupling efficiency. BS produced an up‐regulation of cellular glutathione redox cycling and protected against hypoxia/reoxygenation‐induced apoptosis in H9c2 cells. However, the protective effect of BS against myocardial ischemia/reperfusion injury was seen in female but not male rats ex vivo. The cardioprotection afforded by BS was likely mediated by an up‐regulation of mitochondrial glutathione redox cycling in female rat hearts. In conclusion, the ensemble of results suggests that BS is an active ingredient of Herba Cistanches. The gender‐dependent effect of BS on myocardial protection will further be investigated. Copyright © 2013 John Wiley & Sons, Ltd.